ESPIONAGE IN SALT FILM: A STUDY OF POPULAR LITERATURE - Juli Setyoningrum; Lusia Kristiasih Dwi Purnomosasi (English Teaching Journal : A Journal of English Literature, Language and Education, 2015)
Film is one of the popular literary product that are produced to entertain. Film is the object material for this research study. This research analyzes about espionage in Salt film. It analyzes focus in Espionage that happen in the world. Espionage practices in Salt film are related closely to the espionage in the world. The aim of this research is to analyze why is the espionage still exist up to 21st century. A study of popular literature is chosen by the researcher in order to analyze the research problems. The results of the research are to show that United States is the winner of Cold War with its espionage activity. Salt is an espionage film that contains the high intelligence, secret cover, spy cases, and war of ideology. The development of espionage films where Hollywood always makes United States as the winner is the evident that espionage film is populer. The popularity of espionage films is influenced by the espionage practices in the real world. Espionage in the 21st century still occurs in some countries with difference motives. The purposes of the espionage activities are to show the superiority, power and existence of some countries especially United States as an international police in the world.